Final answer:
To transform the given equation into a system of first-order equations, we can use the definitions x1 = u, x2 = u', x3 = u'', and x4 = u'''. The corresponding system of equations is: a) x1' = x2, b) x2' = x3, c) x3' = x4, d) x4' = 0.
Step-by-step explanation:
To transform the given equation into a system of first-order equations, let's define the variables as follows: x1 = u, x2 = u', x3 = u'', and x4 = u'''. The given equation is u(4) - u = 0. To express this equation in terms of the new variables, we have:
a) x1' = x2
b) x2' = x3
c) x3' = x4
d) x4' = 0